Impact-resistant glass bottle and preparation method thereof
By using nano-silica aerosol deposition technology to form a potassium-boron-rich layer on the surface of glass bottles and a three-stage heat treatment process, the limitations of traditional strengthening methods in glass bottle manufacturing have been overcome, achieving a highly efficient improvement in impact resistance.
Patent Information
- Application Number
- CN202511060013.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-11-11
AI Technical Summary
Existing technologies cannot achieve deep and integrated modification of the microstructure of the surface and subsurface of glass bottles without significantly increasing process complexity and manufacturing costs, thereby improving impact resistance. Traditional strengthening methods have limitations in glass bottle manufacturing.
By forming a potassium-boron-rich layer on the surface of the glass bottle, and using a K2B4O7-loaded nano-silica aerosol deposition technology combined with a three-stage heat treatment process, a BOK-Si strengthening layer is formed, which enhances the compressive stress distribution on the glass surface and forms a stable chemical bond with the substrate.
It significantly improves the impact resistance of glass bottles, with an impact strength of ≥2.5J. The process is simple and suitable for large-scale production, reducing production costs.
Smart Images

Figure CN120923149A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of glass manufacturing and processing technology, and specifically relates to an impact-resistant glass bottle and its preparation method. Background Technology
[0002] In modern industrial manufacturing and daily consumer goods, glass materials occupy an indispensable position due to their excellent chemical stability, transparency, and recyclability. Especially in the packaging industry, glass bottles, as key containers for various liquids and semi-solid materials, have expanded their applications from traditional food and beverages to pharmaceuticals, chemicals, and high-end consumer goods—fields with higher requirements for safety and stability. With the continuous expansion of application scenarios, the requirements for the core performance indicators of glass bottles, especially their mechanical strength, are becoming increasingly stringent. Therefore, developing glass bottles with impact resistance to reduce the risk of breakage during transportation, storage, and use, and to ensure the safety and integrity of their contents, has become a key technical challenge that needs to be addressed in this field.
[0003] To improve the mechanical strength of glass products, various strengthening pathways have been implemented in existing technologies. Among them, introducing a compressive stress layer through surface modification is a recognized effective technique. For example, Chinese Patent CN108689612B discloses a fire-resistant glass and its preparation method. The core technology of this scheme lies in firstly, using a special fire-retardant liquid to chemically treat the surface of the glass substrate, forming a chemically strengthened layer on the glass surface through an ion replacement reaction; subsequently, combined with physical tempering treatment, a stress distribution of internal tension and external compression is further established within the glass. This dual treatment method combining chemical and physical strengthening is designed to construct a protective system that can effectively resist high-temperature thermal shock, thereby maintaining the structural integrity of the glass under extreme conditions such as fires, resulting in a significant improvement in fire resistance. Correspondingly, this compressive stress layer can also provide some resistance to external mechanical impacts at room temperature.
[0004] Another mainstream strengthening technology focuses on the design of composite structures, such as the laminated glass disclosed in Chinese Patent Publication No. CN104512069B. This technology embeds a high-molecular polymer interlayer, such as polyvinyl butyral (PVB), between two or more glass layers, forming a "sandwich"-like layered composite structure. Its working mechanism is that when the glass is impacted, the interlayer, with its excellent toughness and viscoelasticity, absorbs and dissipates a large amount of impact energy. Even if the outer glass breaks, the fragments are firmly adhered to the interlayer, thus preventing flying debris from injuring people and maintaining the basic integrity of the structure. This solution has been widely used in construction, automobiles, and other fields, effectively solving the safety problems of large-size flat glass.
[0005] However, with the increasing demands for impact resistance in glass bottles and the growing emphasis on the economic efficiency of production processes, some inherent characteristics of the aforementioned technical solutions at the principle level have gradually revealed their limitations in addressing the specific scenario of high-performance glass bottle manufacturing. Specifically, the combination of surface chemical strengthening and physical tempering essentially introduces a stress field "passively" based on the original network structure of the glass through differences in ionic radii or heat treatment gradients. This compressive stress layer is typically only on the order of tens of μm in depth. While it can effectively prevent the initiation of microcracks, when the impact energy is sufficient to penetrate or bypass this shallow defense, once the crack enters the internal tensile stress zone, it will rapidly propagate, leading to catastrophic overall fracture. The bottleneck of this technical approach lies in the fact that it primarily optimizes the "skin" strength of the glass, failing to substantially reconstruct and optimize the microscopic network structure of the subsurface region beneath the glass surface, thus limiting its ability to prevent crack depth propagation. Furthermore, specially formulated chemical treatment solutions (such as the aforementioned fire retardant) are often complex in composition and expensive, and their coordination and control with subsequent heat treatment processes are difficult, limiting their application in cost-sensitive large-scale bottle production. On the other hand, while the composite structure principle of laminated glass exhibits excellent energy absorption, its structural form is fundamentally unsuitable for glass bottles with complex curved surfaces and hollow shapes. Manufacturing matching interlayers for such integrated structures as bottle bodies is extremely complex and uneconomical. More importantly, this macroscopic composite approach does not aim to improve the strength of the glass material itself, but rather compensates for the brittleness of the substrate through external additional layers, which is fundamentally contradictory to the development trend of glass bottles pursuing lightweight, high-strength, and integrated designs.
[0006] Current technologies face a technical dilemma: how to achieve deep, integrated modification of the microstructure of the surface and subsurface layers of glass bottles without significantly increasing process complexity and manufacturing costs, thus overcoming the limitations of the traditional strengthening paradigms of surface stress and macrostructure composite. The current technological gap lies in the lack of a preparation method that organically combines the infiltration of surface chemical components with the reconstruction of the matrix microstructure (such as controlled crystallization). This method should be able to form a strengthening layer on the glass surface, possessing surface compressive stress that resists crack initiation, thereby improving the ability to resist crack initiation and propagation.
[0007] Therefore, how to improve the impact resistance of glass bottles while taking into account the operability and economy of the process has become a key challenge and a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0008] To address the aforementioned problems, this invention provides a novel impact-resistant glass bottle and its preparation method. By optimizing the glass material formulation and preparation process, the impact resistance of the glass bottle is significantly improved, while also being compatible with existing production equipment and having low process difficulty.
[0009] The technical solution of the present invention is an impact-resistant glass bottle, comprising a silicate glass substrate and a reinforcing layer 8-10 μm thick on the surface of the silicate glass substrate. By mass fraction, the silicate glass substrate is composed of: B2O3 8%-12%, Na2O 10%-14%, K2O 2%-5%, MgO 3%-5%, CaO 2%-3%, with the balance being SiO2 and unavoidable impurities.
[0010] The impact-resistant glass bottle disclosed in this invention has significantly different features compared to traditional glass bottles. Traditional glass bottles have smooth surfaces and relatively simple microstructures, while the impact-resistant glass bottle mentioned in this invention features a potassium-boron-rich layer on its surface for reinforcement. This layer is formed through the deposition of nano-silica aerosol loaded with K₂B₄O₇ during the preparation process. After deposition, high-temperature treatment causes K₂B₄O₇ to decompose into potassium oxide and boron oxide, which diffuse into the glass surface to form a BOK-Si reinforcing layer. This reinforcing layer not only enhances the compressive stress distribution on the glass surface and reduces the surface sodium ion concentration, but also forms a composite network with the loaded silica, further improving the impact resistance of the glass bottle.
[0011] It is worth noting that this solution is essentially a reinforcement process, so the upper limit of performance depends on the strength of the glass bottle substrate and the bonding effect between the reinforcement layer and the substrate. Therefore, it is essential to first ensure that the glass bottle substrate has good impact resistance.
[0012] This invention further discloses a method for preparing the above-mentioned impact-resistant glass bottle, comprising the following steps: Step (1): Mix the silicate glass raw materials according to the formula and melt them at 1450-1550℃ to obtain glass melt; Step (2): The glass melt is blown into a bottle preform at 1100-1200℃, the blowing pressure is controlled at 0.4-0.6MPa, the mold preheating temperature is 300-400℃, and after forming, it is immediately placed in an annealing furnace at 550-600℃ and heated to 570-590℃ at 3-5℃ / min and held for 8-15min, and then cooled to below 300℃ at 2-3℃ / min. Step (3): Raise the temperature of the preform to 630-670℃, and deposit the nano-silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.5-1.0L / min, deposition distance 10-15cm, nozzle pressure 0.2MPa, deposition time 8-10s, and after deposition, keep it at 650-700℃ for 8-13min to promote component penetration. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 500-550℃ for 15-20 minutes; b. Crystallization stage: Hold at 600-650℃ for 30-40 minutes; c. Strengthening stage: Hold at 400-450℃ for 60-90 minutes, and then cool to obtain an impact-resistant glass bottle.
[0013] This solution is applicable to various silicate glass systems. The introduction of B2O3 can lower the softening point of the glass and improve the matching of thermal expansion coefficients, thereby reducing stress concentration during heat treatment.
[0014] Preferably, in step (2), the temperature of the glass melt in the blow molding process is 1150-1180℃, the blowing pressure is 0.45-0.55MPa, the mold preheating temperature is 320-380℃, the heating rate of the annealing furnace is 5±1℃ / min, the annealing temperature is 580±10℃, and the holding time is 15±2min.
[0015] In the blow molding process, precise control of mold preheating temperature and blowing pressure can ensure that the preform wall thickness deviation is ≤0.2mm and the surface is free of scratches or bubbles >5μm, thus providing a good foundation for subsequent modification treatment.
[0016] Preferably, in step (3), the preparation method of the deposition liquid is as follows: nano-silica (particle size 20-50nm) and anhydrous K2B4O7 (K2B4O7, purity ≥99.9%) are mixed at a mass ratio of 10:1.0-1.5, anhydrous ethanol (water content ≤0.01%) is added, and the mixture is dispersed by ultrasonic waves at 40kHz for 30min in a dry argon atmosphere to obtain a stable deposition liquid with a solid content of 3%-8%.
[0017] During the preparation of aerosols, ultrasonic dispersion can effectively prevent the agglomeration of nanoparticles and ensure uniform particle distribution during deposition.
[0018] Preferably, in step (3), the surface temperature of the preform is 630-670℃, which is higher than the decomposition temperature of K2B4O7 (≥600℃). During the deposition process, K2B4O7 decomposes to generate active components K2O and B2O3. The temperature in step (3) must meet the requirements of K2B4O7 decomposition and prevent the glass bottle substrate from reaching a viscous flow state that would cause deformation.
[0019] After deposition and heat preservation, K2O and B2O3 diffuse into the glass surface through high temperature, forming a BOK-Si strengthening layer.
[0020] Preferably, in step (4), the nucleation stage is held at 520-540℃ for 18-20 min to promote the formation of the BOK-Si network; the crystallization stage is held at 620-640℃ for 35-40 min to induce ion exchange between potassium and sodium ions and generate nano-sized borosilicate crystals; and the strengthening stage is held at 420-440℃ for 70-90 min to make the surface compressive stress ≥150MPa.
[0021] The three-stage heat treatment process can effectively control the microstructure of the strengthening layer. The nucleation stage promotes the formation of the BOK-Si strengthening layer network, the crystallization stage generates nanoscale crystals, and the strengthening stage increases the surface compressive stress, thereby significantly enhancing the impact resistance of the glass bottle.
[0022] Step 1: Preparation and Homogenization of High Borosilicate Glass Raw Materials. First, accurately weigh the glass raw materials according to the specified mass percentages. Place these components in a V-type mixer and dry mix at 40 rpm for 60 minutes to ensure uniform distribution of each component on a macroscopic scale. Then, transfer the homogenized raw materials into a continuous electric melting furnace and melt them within a temperature range of 1500°C to 1550°C. At this temperature, the raw materials completely melt to form a glass melt with Newtonian fluid properties. To ensure a high degree of consistency in the chemical composition and physical properties of the glass melt throughout the melt, a mechanical stirring system and a bubbling system are activated. The mechanical stirring system uses a platinum-rhodium alloy impeller to force convection stirring of the melt at a speed of 10 to 15 rpm; simultaneously, dry, high-purity argon gas is introduced into the bottom of the melt to form an upward bubble flow, further promoting the clarification and homogenization of the melt. The entire melting and homogenization process lasts 24 to 36 hours until the bubble content in the molten glass is below 0.1 bubbles / cm³, and the viscosity fluctuation range measured by a high-temperature viscometer is less than ±2%. This step employs a glass formulation with a high boron (B₂O₃) and specific alkali metal oxide (Na₂O, K₂O) ratio. The purpose is not only to adjust the glass's forming properties, but more importantly, to provide the necessary reactive species (sodium ions) and network structure (boron-rich network) for subsequent in-situ surface reactions and ion exchange processes. This is a technical prerequisite for realizing a surface gradient microcomposite structure.
[0023] Step two: Precision blow molding and stress pretreatment of the glass preform. High-temperature molten glass, homogenized and heated to between 1150°C and 1180°C, is drawn through a feed channel and sheared into droplets of predetermined mass. These droplets enter the initial mold, where pressure is applied by a plunger and initial air blowing to form a preform with a precise mouth structure and preliminary cavity. The preform is then transferred to the finishing mold for final blow molding under a constant blowing pressure of 0.45 to 0.55 MPa. To ensure uniform bottle wall thickness, the inner wall of the finishing mold is precision machined, and the mold temperature is strictly controlled within a preheating range of 320°C to 380°C. After demolding, the surface temperature of the formed glass bottle is approximately 650°C, at which point it is immediately sent to a continuous annealing furnace. The annealing process comprises three strictly controlled stages: First, the glass bottle is heated from its current temperature to an annealing temperature of 580℃±10℃ at a rate of 5℃ per minute. Then, it is held at this temperature for 15±2 minutes. This process aims to completely eliminate the internal thermal stress generated during blow molding and rapid cooling, resulting in a substrate with uniform stress and no macroscopic defects. Finally, it is slowly cooled to below 300℃ at a rate of 3℃ per minute, followed by natural cooling. This step ensures that the resulting glass preform has a uniform wall thickness, with the difference between the maximum and minimum wall thickness not exceeding 0.2 mm, and that its inner and outer surfaces are free of defects such as scratches, bubbles, or stones larger than 5 μm. This provides a high-quality, defect-free reaction substrate for subsequent surface modification treatments.
[0024] Step 3: Loading and interfacial penetration of the surface-reactive nano-precursor. This step is one of the core technical aspects of this invention. First, a functionalized nanocomposite deposition solution is prepared. The preparation process of this deposition solution is as follows: hydrophilic fumed silica (SiO2) powder with an average particle size of 30 nm and a specific surface area greater than 200 m² / g is selected as the carrier; anhydrous K₂B₄O₇ powder with a purity higher than 99.9% and vacuum-dried is selected as the core reactant. The nano-silica and anhydrous K₂B₄O₇ are mixed at a mass ratio and added to anhydrous ethanol solvent with a purity of 99.99%, with the solid content controlled at 5% (mass fraction). The mixture is placed in a stainless steel container with a cooling jacket, and under the protection of a temperature below 10°C and a dry argon atmosphere (purity 99.999%), an ultrasonic probe-type dispersion device with a power of 1000W and a frequency of 40kHz is used for energy input and continuous dispersion for 30 min. This high-energy ultrasonic treatment ensures that anhydrous K2B4O7 microparticles are fully dispersed and loaded onto the surface of nano-silica particles. Simultaneously, nano-silica aggregates are broken down, forming a highly stable and uniformly dispersed deposition solution in ethanol. Laser particle size analyzer analysis shows that the D90 particle size of the particles in the deposition solution is less than 100 nm, and the absolute value of the Zeta potential is greater than 40 mV, indicating excellent dispersion stability.
[0025] When the glass preform is cooled to a specific temperature range of 630°C to 670°C in the annealing furnace, it is removed from the furnace and immediately deposited. The selection of this temperature window is crucial: it is higher than the initial decomposition temperature of anhydrous K₂B₄O₇ (approximately 600°C), ensuring in-situ decomposition of the reactants; simultaneously, it is lower than the softening point of glass, preventing deformation of the bottle during processing. An ultrasonic atomization deposition system is used to atomize the prepared nanocomposite deposition liquid into an aerosol with an average particle size of 20 μm. Dry argon gas with a purity of 99.999% is used as the carrier gas, with a flow rate controlled at 0.8 L / min. The distance between the nozzle and the glass bottle surface is maintained at 12 cm, and the deposition pressure is set at 0.2 MPa. A multi-axis robot controls the nozzle to uniformly deposit the nanocomposite onto the rotating glass bottle for 8 seconds. When the droplets of the deposition solution come into contact with the hot glass bottle surface, the ethanol solvent evaporates instantly, and nano-silica particles loaded with K2B4O7 are uniformly deposited on the bottle surface, forming a porous nanostructure film. Simultaneously, due to the surface temperature exceeding 600℃, K2B4O7 undergoes in-situ thermal decomposition, with the chemical reaction K2B4O7(s) → K2O + 2B2O3, generating highly chemically active potassium oxide and boron trioxide.
[0026] After deposition, the glass bottle was immediately returned to a holding furnace set at 680℃ and maintained at that temperature for 10 minutes. This holding process provides sufficient driving force and time for the diffusion of the generated active K₂O and B₂O₃ species into the glass matrix. Under high temperature, these highly active species rapidly penetrate into the glass surface through a porous network composed of nano-silica particles as diffusion channels. They react with the silicon-oxygen network (Si-O-Si) and boron-oxygen network in the glass matrix to form a potassium- and boron-rich BOK-Si infiltrated reinforcing layer with a thickness of 8-10 μm.
[0027] Step four: Multi-stage microstructure evolution and synergistic strengthening heat treatment. The glass bottle treated in step three is placed in a box-type heat treatment furnace with precisely programmable temperature control for continuous, staged, and specific heat treatment. This heat treatment process is another core technical aspect of this invention, aiming to precisely control the evolution of the microstructure within the permeation layer to simultaneously achieve ion exchange compressive stress strengthening and nanocrystalline phase dispersion toughening.
[0028] The first stage is the nucleation stage. The furnace temperature is increased to 530°C at a rate of 20°C per minute and precisely held at this temperature for 20 minutes. Within this temperature range, the viscosity of the glass network is moderate, and the atomic diffusion rate is low. Its main function is to provide a large number of uniformly distributed crystal nuclei for subsequent crystal growth. B2O3 enriched in the permeation layer acts as a strong nucleating agent, reacting with K2O and SiO2 in the matrix to induce the formation of a large number of crystal nuclei on the basis of BOK-Si. Precise temperature control in this stage is crucial to ensuring the fineness and uniformity of the final grains.
[0029] The second stage is the crystallization and ion exchange stage. After nucleation, the furnace temperature is rapidly increased to 630°C at a rate of 15°C per minute and held at this temperature for 40 minutes. This temperature is much higher than the glass transition temperature, significantly enhancing ion migration. Two key physicochemical processes occur simultaneously in this stage: First, nanocrystal growth. At the higher temperature, the nuclei formed in the first stage begin to grow, forming a thermodynamically more stable nanoscale crystalline phase. X-ray diffraction (XRD) analysis identified this crystalline phase as a high-toughness potassium borosilicate (e.g., K₂O·B₂O₃·4SiO₂) microcrystal. Due to the high nucleation density and controlled growth, the final crystal size is limited to the range of 30 to 80 nm, and it is embedded in the original amorphous glass matrix in a diffuse distribution, forming a typical nanocrystalline / amorphous glass composite structure. Second, chemical ion exchange. At this temperature, a large chemical potential gradient exists between the high concentration of potassium ions (potassium ions, ionic radius 1.38 Å) derived from the decomposition of K₂O in the permeation layer and the sodium ions (sodium ions, ionic radius 1.02 Å) inherent in the glass matrix. Constrained by the principle of electroneutrality, potassium ions and sodium ions undergo one-to-one interdiffusion exchange. Because the ionic radius of potassium ions is much larger than that of sodium ions, when larger potassium ions "squeeze" into the network voids previously occupied by smaller sodium ions, they exert a strong compressive effect on the surrounding glass network structure, thereby introducing a uniformly distributed residual compressive stress field on the glass surface.
[0030] The third stage is the stress stabilization and strengthening stage. After the crystallization and ion exchange processes are completed, the furnace temperature is slowly reduced to 430°C at a rate of 5°C per minute, and then held at this temperature for 80 minutes. The purpose of this step is to perform structural relaxation and stabilization treatment on the compressive stress field formed in the second stage. Prolonged low-temperature annealing effectively eliminates micro-stress concentrations that may be caused by uneven ion exchange or improper cooling rates, making the compressive stress distribution on the entire surface layer more uniform and stable, and maximizing its value. Non-contact measurement using a photoelastic stress meter shows that the final stable compressive stress value formed on the glass bottle surface is no less than 150 MPa.
[0031] Compared with the prior art, the present invention has the following advantages: 1. This invention significantly improves the impact resistance of glass bottles by introducing nano-silica aerosol loaded with K2B4O7 and combining it with a three-stage heat treatment process, achieving an impact strength ≥2.5J.
[0032] 2. The reinforcing layer used in this invention forms a stable chemical bond with the glass substrate, has a uniform thickness, and is simple to prepare. It can be adapted to large-scale production, reduces the production cost of impact-resistant glass bottles, and provides a new path for the development of high-performance glass products. Attached Figure Description The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0033] Figure 1 This is a magnified image of a cross-section of the bottle from Example 1 under a 500x microscope, showing the reinforcing layer and the substrate. Detailed Implementation The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0034] First, the silicate glass raw materials are mixed according to the mass fraction ratio. During the mixing process, a high-precision electronic scale must be used to weigh the raw materials to ensure that the proportion of each component is accurately controlled within ±0.1%. The mixed raw materials are then put into a furnace and melted at a temperature of 1450-1550℃ for 2-3 hours to ensure that the raw materials react fully and form a homogeneous glass melt.
[0035] After melting, the molten glass is transferred to a blow molding machine to form bottle preforms through a blow molding process. During the blow molding process, the temperature of the molten glass needs to be controlled between 1100-1200℃, preferably between 1150-1180℃, while the mold preheating temperature is set at 300-400℃, preferably between 320-380℃. The blowing pressure is set at 0.4-0.6MPa, preferably between 0.45-0.55MPa, to ensure uniform preform wall thickness and no obvious defects. Immediately after forming, the preform is placed in an annealing furnace with a heating rate of 5℃ / min. After heating to 580℃, it is held for 15 minutes, and then cooled to below 300℃ at a rate of 3℃ / min to complete the initial stress relief.
[0036] After annealing, the preform enters the strengthening layer preparation stage. At this stage, the surface temperature of the preform needs to be controlled between 630-670℃, higher than the decomposition temperature of K2B4O7, to ensure effective diffusion of the active components during subsequent deposition. K2B4O7-loaded nano-silica aerosol is uniformly deposited onto the preform surface using a deposition device. Deposition parameters include a carrier gas flow rate of 0.5-1.0 L / min, a deposition distance of 10-15 cm, a nozzle pressure of 0.2 MPa, and a deposition time of 8-10 s. After deposition, the preform is held at 650-700℃ for 10 min to promote the penetration of the coating components into the glass substrate, forming an 8-10 μm strengthening layer.
[0037] The preparation process of K₂B₄O₇-loaded nano-silica aerosol is as follows: First, nano-silica with a particle size of 20-50 nm is mixed with anhydrous K₂B₄O₇ at a mass ratio of 10:1.0-1.5, and anhydrous ethanol with a water content ≤0.01% is added as a dispersion medium. The mixture is dispersed by ultrasonication at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution. This deposition solution is atomized by a deposition device to form an aerosol. During the deposition process, ultrasonic dispersion can effectively prevent the agglomeration of nanoparticles, thereby ensuring that the particles are uniformly distributed on the surface of the preform.
[0038] After deposition, the preform undergoes a three-stage heat treatment process. The nucleation stage temperature is set at 500-550℃, preferably 520-540℃, with a holding time of 15-20 min, preferably 18-20 min. During this stage, the active components K₂O and B₂O₃ react with the Si-O network in the glass matrix to form a BOK-Si reinforcing layer network structure. The crystallization stage temperature is set at 600-650℃, preferably 620-640℃, with a holding time of 30-40 min, preferably 35-40 min. During this stage, nanoscale borosilicate crystals with a particle size of 20-50 nm are induced through potassium and sodium ion exchange. The strengthening stage temperature is set at 400-450℃, preferably 420-440℃, with a holding time of 60-90 min, preferably 70-90 min. This stage significantly increases the surface compressive stress to ≥150MPa, while optimizing the microstructure of the reinforcement layer.
[0039] Throughout the preparation process, precise control of various process parameters has a significant impact on the performance of the final product. For example, the selection of carrier gas flow rate and deposition distance during deposition directly affects the uniformity and adhesion of the coating, while the temperature and time of the three-stage heat treatment process determine the microstructure and mechanical properties of the reinforced layer. Furthermore, achieving a preform surface roughness Ra≤0.05μm depends on the precise control of the preheating temperature of the mold and the blowing pressure before deposition, as well as the optimization of the post-deposition heat treatment process.
[0040] General Implementation Examples A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: The silicate glass raw materials are mixed according to the following ratio: B2O3 8%-12%, Na2O 10%-14%, K2O 2%-5%, MgO 3%-5%, CaO 2%-3%, with the balance being SiO2 and unavoidable impurities. The mixture is then melted at 1450~1550℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1100-1200℃, the blowing pressure is controlled at 0.4-0.6MPa, the mold preheating temperature is 300-400℃, and after forming, it is immediately placed in an annealing furnace at 550-600℃ and heated to 570-590℃ at 3-5℃ / min and held for 8-15min, and then cooled to below 300℃ at 2-3℃ / min. Step (3): Raise the temperature of the preform to 630-670℃, and deposit the nano-silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.5-1.0L / min, deposition distance 10-15cm, nozzle pressure 0.2MPa, deposition time 8-10s, and after deposition, keep it at 650-700℃ for 8-13min to promote component penetration. The preparation method of the deposition solution is as follows: nano-silica with a particle size of 20-50nm is mixed with anhydrous K2B4O7 at a mass ratio of 10:1.0-1.5, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40kHz for 30min in a dry argon atmosphere to obtain the deposition solution. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 500-550℃ for 15-20 minutes; b. Crystallization stage: Hold at 600-650℃ for 30-40 minutes; c. Strengthening stage: Hold at 400-450℃ for 60-90 minutes, and then cool to obtain an impact-resistant glass bottle.
[0041] Example 1 A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 9s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, then cool to obtain impact-resistant glass bottles, such as... Figure 1 As shown, the bonding between the reinforcing layer and the substrate is uniform, with no obvious pores or delamination, and the thickness is approximately 8.5 ± 0.3 μm.
[0042] Example 2 A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 67%, B2O3 12%, Na2O 10%, K2O 4.2%, MgO 3%, CaO 3%, with the remainder being unavoidable impurities. The mixture is then melted at 1450℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1100℃, the blowing pressure is controlled at 0.45MPa, the mold preheating temperature is 320℃, and after forming, it is immediately placed in an annealing furnace at 550℃ and heated to 570℃ at 4℃ / min and held for 13min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 630℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.5L / min, deposition distance 15cm, nozzle pressure 0.2MPa, deposition time 10s, and after deposition, keep warm at 650℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 50 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.0, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 4%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 500℃ for 20 minutes; b. Crystallization stage: Hold at 600℃ for 40 minutes; c. Strengthening stage: Hold at 400℃ for 90 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0043] Example 3 A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 72%, B2O3 8%, Na2O 12%, K2O 2%, MgO 3.3%, CaO 2%, with the remainder being unavoidable impurities. The mixture is then melted at 1550℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1200℃, the blowing pressure is controlled at 0.55MPa, the mold preheating temperature is 380℃, and after forming, it is immediately placed in a 600℃ annealing furnace and heated to 590℃ at 6℃ / min and held for 17min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 670℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 1.0L / min, deposition distance 10cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 700℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 20 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.5, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 7%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 550℃ for 15 minutes; b. Crystallization stage: Hold at 650℃ for 30 minutes; c. Strengthening stage: Hold at 450℃ for 60 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0044] Example 4 A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: The silicate glass raw materials are mixed according to the following ratio: SiO2 70%, B2O 39%, Na2O 11%, K2O 2.5%, MgO 4.5%, CaO 2.2%, with the remainder being unavoidable impurities. The mixture is then melted at 1500℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1170℃, the blowing pressure is controlled at 0.52MPa, the mold preheating temperature is 360℃, and after forming, it is immediately placed in an annealing furnace at 590℃ and heated to 585℃ at 5.5℃ / min and held for 16min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 660℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.9L / min, deposition distance 11cm, nozzle pressure 0.2MPa, deposition time 9s, and after deposition, keep warm at 680℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 25 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.4, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 540℃ for 16 minutes; b. Crystallization stage: Hold at 640℃ for 32 minutes; c. Strengthening stage: Hold at 430℃ for 70 minutes, and obtain impact-resistant glass bottles after cooling.
[0045] Example 5 A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 11%, Na2O 11%, K2O 3.5%, MgO 3.8%, CaO 2.5%, with the remainder being unavoidable impurities. The mixture is then melted at 1470℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1120℃, the blowing pressure is controlled at 0.48MPa, the mold preheating temperature is 340℃, and after forming, it is immediately placed in an annealing furnace at 560℃ and heated to 575℃ at 4.5℃ / min and held for 14min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 640℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.6L / min, deposition distance 14cm, nozzle pressure 0.2MPa, deposition time 9s, and after deposition, keep warm at 660℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 45nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.1, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40kHz for 30min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 4%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 510℃ for 19 minutes; b. Crystallization stage: Hold at 610℃ for 38 minutes; c. Strengthening stage: Hold at 410℃ for 85 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0046] Comparative Example 1 The difference from Example 1 is that there is no reinforcing layer: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown at 1150℃ to form a bottle preform. The blowing pressure is controlled at 0.5MPa and the mold preheating temperature is 350℃. After forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min. Then it is cooled to below 300℃ at 3℃ / min. After cooling, an impact-resistant glass bottle is obtained.
[0047] Comparative Example 2 The difference from Example 1 is that K2B4O7 was not added: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): When the bottle preform temperature is raised to 650℃, nano-silica aerosol is deposited on the bottle surface. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, it is kept at 670℃ for 10min to promote component penetration. The preparation method of nano-silica aerosol is as follows: nano-silica with a particle size of 30nm is added to anhydrous ethanol and dispersed by ultrasonic waves at 40kHz for 30min in a dry argon atmosphere to obtain a stable deposition liquid with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0048] Comparative Example 3 The difference from Example 1 is that no nano-silica was added as a carrier: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): When the preform temperature is raised to 650℃, K2B4O7 load is deposited on the surface of the bottle. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, it is kept at 670℃ for 10min to promote component penetration. The sedimentation solution was prepared by adding anhydrous K2B4O7 to anhydrous ethanol at a mass ratio of 1:200 to obtain the sedimentation solution. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0049] Comparative Example 4 The difference from Example 1 is that the reinforcing layer is prepared by a coating method: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to room temperature at 3℃ / min. Step (3): Use a brush to coat the sediment onto the surface of the bottle; The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0050] Comparative Example 5 The difference from Example 1 is that the post-deposition holding time is 5 minutes: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 5min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0051] Comparative Example 6 The difference from Example 1 is that the nano-silica and anhydrous K2B4O7 are mixed in a mass ratio of 10:0.8: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:0.8, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0052] Comparative Example 7 The difference from Example 1 is that in step (3): deposition occurs when the preform temperature is increased to 550°C. A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Increase the temperature of the preform to 550℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0053] Comparative Example 8 The difference from Example 1 is that in step (3): deposition occurs when the preform temperature is increased to 750°C. A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Increase the temperature of the preform to 750℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0054] Comparative Example 9 The difference from Example 1 is that in step (4): the preform with the loaded deposition layer is only kept at 630°C for 35 minutes. A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): Heat-treat the preform with the loaded deposited layer. Hold at 630℃ for 35 minutes, then cool to obtain an impact-resistant glass bottle.
[0055] Comparative Example 10 The difference from Example 1 lies in the matrix composition: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 70%, B2O 37%, Na2O 15%, K2O 2.2%, MgO 3%, CaO 2.5%, with the remainder being unavoidable impurities. The mixture is then melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min, and then cooled to below 300℃ at 3℃ / min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0056] Comparative Example 11 The difference from Example 1 is that in step (2), after the annealing furnace is kept at 580°C, step (3) is immediately initiated: A method for preparing an impact-resistant glass bottle includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed according to the following ratio: SiO2 68%, B2O3 10%, Na2O 11%, K2O 4.2%, MgO 4%, CaO 2.5%, with the remainder being unavoidable impurities. After mixing, the mixture is melted at 1480℃ to obtain glass melt. Step (2): The glass melt is blown into a bottle preform at 1150℃, the blowing pressure is controlled at 0.5MPa, the mold preheating temperature is 350℃, and after forming, it is immediately placed in an annealing furnace at 580℃ and heated to 580℃ at 5℃ / min and held for 15min. Step (3): Raise the temperature of the preform to 650℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. The deposition parameters are: carrier gas (argon) flow rate 0.8L / min, deposition distance 12cm, nozzle pressure 0.2MPa, deposition time 8s, and after deposition, keep warm at 670℃ for 10min to promote component penetration. The preparation method of the deposition solution is as follows: 30 nm nano-silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.2, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain a stable deposition solution with a solid content of 5%. Step (4): The preform with the loaded deposited layer is heat-treated in three stages: a. Nucleation stage: Hold at 520℃ for 18 minutes; b. Crystallization stage: Hold at 630℃ for 35 minutes; c. Strengthening stage: Hold at 420℃ for 75 minutes, and after cooling, obtain an impact-resistant glass bottle.
[0057] Upright glass bottles (50mm in diameter) were prepared according to the examples and comparative examples. Testing methods: Reinforcing layer thickness: Broken bottle fragments were embedded in bakelite powder, the cross-section was polished, and then etched with 4% hydrofluoric acid for 10 seconds. After cleaning, it was etched with 10% sodium hydroxide solution for 20 seconds, cleaned, and dried. The thickness of the reinforcing layer was measured under a 500x optical microscope. Figure 1 As shown.
[0058] Surface compressive stress: Surface compressive stress was measured using a surface stress meter (FSM-6000LE) under conditions of 25℃ and 50% air humidity. Mechanical impact resistance: The glass bottle is placed in a standard sandbag (5kg) and dropped freely from different heights onto a hard surface (cement slab), and the height of the first breakage is recorded; the impact strength of the pendulum is also tested according to GB / T 6552-2015.
[0059] The test results are shown in Table 1.
[0060] Table 1. Test results for comparative examples and implementation examples.
[0061] This invention's impact-resistant glass bottle achieves integrated performance enhancement from matrix network reinforcement to surface gradient structure construction through deep coupling of component design and process innovation. At the component level, a borosilicate system with SiO2 and B2O3 as its core constructs a stable network, while the mixed alkali effect of Na2O and K2O significantly inhibits alkali metal ion migration, improving the intrinsic fracture toughness of the matrix. At the process level, the key breakthrough lies in the deposition of K2B4O7-loaded nano-silica aerosol at 630–670℃: the nano-carrier (particle size 20–50 nm) forms diffusion channels, allowing the active K2O / B2O3 components generated from the decomposition of K2B4O7 to penetrate 5–10 μm into the subsurface layer, forming a BOK-Si transition layer. During this process, boron ions fill vacancies in the silicon-oxygen network through boron-oxygen tetrahedra, while the difference in ionic radius generated by potassium ions replacing sodium ions initially establishes a surface compressive stress field. The subsequent three-stage heat treatment further achieves synergistic strengthening: the nucleation stage (520~540℃) utilizes B2O3 to induce the formation of K2O·B2O3·4SiO2 crystal nuclei; the crystallization stage (620~640℃) simultaneously drives nanocrystal growth and deep ion exchange, with nanocrystals pinning cracks through grain boundary deflection, while potassium / sodium ion exchange maximizes compressive stress; the strengthening stage (420~440℃) stabilizes the surface compressive stress to ≥150MPa through stress relaxation. This triple mechanism of chemical infiltration-crystallization toughening-compressive stress stabilization enables the glass bottle to achieve an impact strength of 2.9J, significantly improved compared to the substrate (Comparative Example 1), and the strengthening layer and the substrate form a seamless transition through chemical bonding (e.g., Figure 1 As shown in the figure, it fundamentally solves the bottleneck problem of traditional shallow reinforcement being easily penetrated by cracks.
[0062] The root cause of failure in the comparative examples lies in the defects of key processes or components that disrupt the integrity of the gradient reinforcement layer, leading to attenuation of the compressive stress field or the absence of crack-blocking mechanisms. Comparative Example 1, similar to conventional processes, suffers from a complete lack of a reinforcement layer, resulting in unimpeded propagation of surface microcracks under impact and a sharp drop in impact strength to 0.5 J. Comparative Example 2, lacking K2B4O7, suffers from insufficient ion exchange, and the BO-Si network remains unreinforced, resulting in a compressive stress of only 150 MPa. Comparative Example 3, omitting the nano-SiO2 support, results in direct K2B4O7 deposition, leading to insufficient penetration depth and uneven distribution, reducing the compressive stress to 100 MPa. Comparative Example 4, employing a coating method, causes localized stress concentration due to deposition liquid accumulation, resulting in a compressive stress of only 80 MPa. Comparative Example 5, reducing the deposition holding time to 5 min, leads to insufficient K2O / B2O3 diffusion, thinning the reinforcement layer and causing a 28% loss in compressive stress. Comparative Example 6, reducing the K2B4O7 ratio (10:0.8), results in insufficient active ion concentration, weakening the compressive stress to 180 MPa. Comparative Example 7 was deposited at 550℃ (below the K2B4O7 decomposition threshold of 600℃), resulting in a low K2B4O7 decomposition rate and a surface compressive stress of only 120 MPa. Comparative Example 8, deposited at 750℃, exceeded the glass softening point, causing matrix deformation and blocking diffusion channels, leading to a drop in compressive stress to 90 MPa. Comparative Example 9 underwent only a single-stage heat treatment, lacking nucleation and crystallization processes, resulting in the absence of nanocrystalline pinning effect; although it retained 200 MPa of compressive stress, the toughening mechanism failed. Comparative Example 10, with a matrix containing as much as 15% Na2O, caused thermal expansion mismatch; microcracks at the reinforced layer / matrix interface resulted in a compressive stress of 280 MPa, but the impact strength remained limited to 2.0 J. Comparative Example 11, without slow cooling after annealing, generated residual thermal stress, leading to residual thermal stress in the matrix, interfering with the formation of the stress field in the deposited layer. Microcrack nucleation during deposition reduced the compressive stress to 240 MPa and created concentrated weak points. These cases collectively demonstrate that any deviation that disrupts the depth of chemical penetration, crystal phase evolution, or stress field stability will degrade the impact performance to the level of conventional glass.
[0063] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An impact-resistant glass bottle, characterized in that, It includes a silicate glass substrate and a reinforcing layer 8-10 μm thick on the surface of the silicate glass substrate. By mass fraction, the composition of the silicate glass substrate is: B2O3 8%-12%, Na2O 10%-14%, K2O 2%-5%, MgO 3%-5%, CaO 2%-3%, with the balance being SiO2 and unavoidable impurities.
2. The impact-resistant glass bottle as described in claim 1, characterized in that, The silicate glass substrate is composed of: 10% B2O3, 11% Na2O, 4.2% K2O, 4% MgO, 2.5% CaO, with the balance being SiO2 and unavoidable impurities; the thickness of the reinforcing layer is 8-9 μm.
3. A method for preparing an impact-resistant glass bottle as described in any one of claims 1-2, characterized in that, Includes the following steps: Step (1) Raw material mixing and melting: Silicate glass raw materials are mixed and melted according to the formula to obtain glass liquid; Step (2) Preform preparation: The glass melt is blown into a preform, kept at 570-590℃ for 8-15 minutes, and then cooled to below 300℃ at 2-3℃ / min. Step (3) Deposition of reinforcement layer: Increase the temperature of the preform to 630-670℃, and deposit the nano silica aerosol loaded with K2B4O7 onto the surface of the bottle through the deposition liquid. After deposition, keep it at 650-700℃ for 8-13 minutes to obtain the preform with the loaded deposition layer. The solid content of the deposition liquid is 3%-8%, the solvent is anhydrous ethanol, and the solid phase particles are nano-silica and anhydrous K2B4O7 in a mass ratio of 10:1.0-1.
5. Step (4) Preparation: The preform with the loaded deposited layer is heat-treated in three stages and cooled to obtain an impact-resistant glass bottle.
4. The method for preparing an impact-resistant glass bottle as described in claim 3, characterized in that, In step (2), the blow molding process is as follows: the glass melt temperature is 1100-1200℃, the blowing pressure is controlled at 0.4-0.6MPa, the mold preheating temperature is 300-400℃, and after molding, it is immediately placed in an annealing furnace at 550-600℃ and heated to 570-590℃ at 3-5℃ / min and held for 8-15min, and then cooled to below 300℃ at 2-3℃ / min.
5. The method for preparing an impact-resistant glass bottle as described in claim 3, characterized in that, In step (3), the deposition parameters are: carrier gas flow rate 0.5-1.0 L / min, deposition distance 10-15 cm, nozzle pressure 0.2 MPa, and deposition time 8-10 s.
6. The method for preparing an impact-resistant glass bottle as described in claim 3, characterized in that, In step (3), the preparation method of the deposition liquid is as follows: nano silica and anhydrous K2B4O7 are mixed at a mass ratio of 10:1.0-1.5, anhydrous ethanol is added, and the mixture is dispersed by ultrasonic waves at 40 kHz for 30 min in a dry argon atmosphere to obtain the deposition liquid.
7. The method for preparing an impact-resistant glass bottle as described in claim 6, characterized in that, The particle size of nano-silica is 20-50nm.
8. The method for preparing an impact-resistant glass bottle as described in claim 3, characterized in that, The three-stage heat treatment in step (4) is as follows: a. Nucleation stage: Hold at 500-550℃ for 15-20 minutes; b. Crystallization stage: Hold at 600-650℃ for 30-40 minutes; c. Strengthening stage: Hold at 400-450℃ for 60-90 minutes.
9. The method for preparing an impact-resistant glass bottle as described in claim 3, characterized in that, The melting temperature in step (1) is 1450~1550℃.
Citation Information
Patent Citations
Laminated glass
CN104512069B
Fireproof glass
CN108689612B